Highly Uniform Trilayer Molybdenum Disulfide for Wafer‐Scale Device Fabrication. (19th August 2014) - Tarasov, Alexey; Campbell, Philip M.; Tsai, Meng‐Yen; Hesabi, Zohreh R.; Feirer, Janine; Graham, Samuel; Ready, W. Jud; Vogel, Eric M.
<x xml:space="preserve">Abstract</x> Molybdenum disulfide (MoS2) is a layered semiconducting material with a tunable bandgap that is promising for the next generation nanoelectronics as a substitute for graphene or silicon. Despite recent progress, the synthesis of high‐quality and highly uniform MoS2 on a large scale is still a challenge. In this work, a temperature‐dependent synthesis study of large‐area MoS2 by direct sulfurization of evaporated Mo thin films on SiO2 is presented. A variety of physical characterization techniques is employed to investigate the structural quality of the material. The film quality is shown to be similar to geological MoS2, if synthesized at sufficiently high temperatures (1050 °C). In addition, a highly uniform growth of trilayer MoS2 with an unprecedented uniformity of ±0.07 nm over a large area (> 10 cm2) is achieved. These films are used to fabricate field‐effect transistors following a straightforward wafer‐scale UV lithography process. The intrinsic field‐effect mobility is estimated to be about <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ch0pnf1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />6.5±2.2</alternatives> cm2 V–1 s–1 and compared to previous studies. These results represent a significant step towards application of MoS2 in nanoelectronics and sensing.